#TITLE_ALTERNATIVE# - HERAWATI (NIM 20506033), SUSI
A buffer solution is a mixture of a weak acid or base and its conjugation which can maintain pH around buffer capacity area. That is pH = pKa±1. The purpose of this research is to prepare buffer solutions of pH 4 to 10 and to examine the ability of buffer solution to maintain pH under the addition of acid or base solutions. Two methods were used: firstly is continuous variation method, the buffer solution was mixed with acid or base solution in several variety of volume ratios. Secondly is dilution method, the buffer dilution was diluted with water until its concentration was 100 times lower. Then the acid or base solutions were added until exceeding pH capacity area. The buffer solution was made of citrate and phosphate compounds. The equivalent mixture of citrate acid and its sodium salt yields pH 4. While equivalent mixture of dihydrogen phosphate and monohydrogen phosphate yields pH 6. The buffer solutions of pH 8 and 10 were made of phosphate salts in several ratios. The buffer solution made of citrate compounds showed pH 0.3-0.4 units lower than the expected values. On the other hand, the buffer solution of phosphate compounds showed pH 0.2-0.8 units higher. The mole ratio of additional acid or base solutions to the buffer solutions were found 2:3, 1:4 and 1:9 for pH 4, 6, and 10 respectively. However, for buffer solution of pH 8 the mole ratio of additional acid was 1:4, while for additional base was 1:9. The curve of pH versus additional acid or base volume showed a relatively symmetrical pattern only for pH 6. The buffer dilution from 1 M to 0.01 M showed 0.1-0.6 units pH changes but it was still in the buffer capacity area.